Robert Stenberg's Theory of Triangular Love in Colleen Hoover's All Your Perfects - Jovita Anugrah Santoso; Tri Pramesti (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
This article focuses on An American author of romance and adult fiction, Colleen Hoover shares her ideas about love and marriage in her novel “All Your Perfects